Salvage treatment of a metastatic colorectal cancer with pMMR/MSS in a 21-year-old man: a case report - Li, Xuesong; Liu, Hao; Yu, Zhuo (Frontiers in Oncology, 2025)
In metastatic colorectal cancer (mCRC) patients with proficient mismatch repair (pMMR)/microsatellite stability (MSS), beyond third-line therapies were extremely limited. Here, we reported a case of a 21-year-old male patient with pMMR/MSS mCRC who failed to respond to both first- and second-line treatment and subsequently received non-standard third-line therapy at a local hospital. This patient was referred to our hospital, and we initiated salvage therapies. The fourth-line treatment, including tislelizumab, regorafenib, pemetrexed, and raltitrexed, was administered with a progression-free survival (PFS) of 13 months. Then, this patient received fifth-line treatment with chidamide, fruquintinib, toripalimab, raltitrexed, and nanoparticle albumin-bound paclitaxel with a PFS of 8 months. During the whole treatment, side effects were tolerable and significantly alleviated with appropriate symptomatic therapies. In addition, cystoscopy plus transurethral resection of a metastatic bladder tumor was successfully conducted to halt the bleeding. The sixth-line regimen was started, and he is still under follow-up. Collectively, this patient achieved long-term survival with a high quality of life through therapies beyond the third line.